EVALUATION OF ANTIPSYCHOTIC USE IN SCHIZOPHRENIA PATIENTS IN CENTRAL JAVA PROVINCE - Perwirahayu Aji Saputri, Ika Sutra (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2024)
Schizophrenia is a mental disorder that affects a person’s thinking and perception. In Indonesia, 4.6% of the population experiences serious mental disorders and 11.6% experiences emotional mental disorders. For the Central Java area, there are 13.9% of people who suffer from emotional disorders and 16.67% suffer from serious mental disorders, namely schizophrenia. Giving antipsychotics is still the primary treatment for schizophrenia patients. This study aims to determine the pattern and profile of antipsychotic use in schizophrenia patients. This research is a descriptive-observational study with a cross-sectional design. Data collection was carried out retrospectively using medical record data. The pattern of antipsychotic use in schizophrenia patients was haloperidol (48%), risperidone (30%), and trifluoperazine (22%).